Personal Name as a Marker of a New Semiotic System: Inter-Slavic Parallels (from the National Revival of the 19th c. to Modern Neo-Paganism) - Dmitry Kirillovich Polyakov (Вопросы ономастики)
This article examines naming practices in three different types of situations: during the Czech and Slovak National Revival of the first half of the 19th century, in Russia and the USSR in the 1920s, and in contemporary neo-pagan communities of various Slavic countries. Despite the differences in historical and cultural context, these situations are typologically comparable. Each of them involves the construction of a new sign system, in which new anthroponyms play a key role, along with other linguistic and extra-linguistic phenomena. In all three situations there was an anthroponymic boom, a mass creation of new personal names (neo-anthroponyms) that would be used by the bearer of the new code. The source of motivation for name-making in the National Revival and neo-paganism is the traditional, even archaic set of Slavic patterns, since “Slavicness” is seen as the highest value (cf. the Czech 1830s “patriotic names” Pravoslav, Rodomil, Dobromila, etc., or the neo-pagan names Pravdomir, Budislav, Vitoslav, etc.). Anthroponymic practices of the early Soviet Union, on the contrary, focused primarily on other patterns, such as abbreviation (Kim, Marklen, Vilena, etc.), whaile some new personal names were also created following the traditional “Slavic” patterns (Krasnoslav, Novomir). The use of this word-formational pattern in different cultural situations indicates its continuity and great pragmatic potential.